Prevalence of acetabular labral tears in asymptomatic children - Georgiadis, Andrew G. (J Child Orthop, 2016)
PURPOSE: Magnetic resonance imaging (MRI) is a sensitive, non-invasive modality to diagnose acetabular labral pathology, and the normal variants of the acetabular labrum have been characterized in adults. However, the prevalence of labral pathology in the asymptomatic pediatric population is unknown. METHODS: All pelvic MRIs performed at a large tertiary-care children’s hospital were reviewed during one calendar year (2014). Only patients aged between 2 and 18 years were included, and scans were excluded for hip pain/pathology or technical inadequacy. A blinded pediatric musculoskeletal radiologist read all eligible scans for the presence or absence of a labral tear. RESULTS: Three hundred and ninety-four pelvic MRIs were screened, and patients were excluded for hip pain/pathology (85 subjects), or technical inadequacy (190 subjects). One hundred and eight subjects (216 hips) met the inclusion criteria and were technically adequate for analysis. Labral tears were visualized in three of 216 (1.4 %) hips (two of the 110 subjects; 1.9 %). CONCLUSIONS: There is a low rate of asymptomatic labral pathology by MRI in pediatric patients. The clinical history remains the means of differentiating real labral pathology from spurious imaging findings. LEVEL OF EVIDENCE IV: Case series (prevalence).